Spiritual Leadership and Organizational Citizenship Behavior as Factors Influencing Employee Performance:A Literature Review - Jatmiko Murdiono; Suparno (PT FORMOSA CENDEKIA GLOBAL, 2023)
Employee performance has many factors that can influence it. This study aims to find out and analyze spiritual leadership and organizational citizenship behavior as factors that affect employee performance. This research method is qualitative through a literature review related to spiritual leadership, organizational citizenship behavior, and employee performance. The study results show that spiritual leadership is a leadership style that can be a factor in determining employee performance. Research findings related to organizational citizenship behavior also impact employee performance because of a sense of belonging to the organization or company where employees work, and spiritual leadership can also influence performance through organizational citizenship behavior. This research contributes to opportunities to improve employee performance by applying spiritual leadership styles and organizational citizenship behavior so that future researchers can use and develop research models